Production of High Fructose Syrup (HFS) from glucose derived from oil palm trees a plant design - Madulid, Nasiari M.; Rasco, Raymund B.; Vicente, Michael Q.; Yap, Kristian July R. (Quezon City College of Engineering, University of the Philippines Diliman, 2012)
The design concerns the establishment of a plant that will cater the production of High Fructose Syrup (HFS), which is basically a sweetener for food and beverages, particularly processed and store-bought food. The plant design shows the formation of a product that will be offered into an existing market, demonstrating efficient conversion from the oil palm trunk to glucose and finally, to high-fructose syrup. The production of this plant aims to minimize oil palm tree wastes by utilizing the trunk and processing into a more useful end product.With the continuous increase in the price of table sugar, other alternative are finding its way across the market. Since HFS is cheaper than table sugar, it serves as substitute for table sugar in several US households. The demand for products that uses HFS-42 in the Philippines shows an increasing market size. Due to several industries that use HFS in their process such as canned good and ice cream, the increase in market size results to a consequent increase in demand of HFS-42.For every 23 480 688.37 kg of oil palm trunk that is harvested, 3 502 300.02 kg of syrup is obtained. The conversion rate is low, but because of the nature of the plant and its processes, it can still be profitable. First, the oil palm trunk is obtained from the plantation and acquisition if free. Also, most of the other chemicals and materials used in the process can be reused, such as the Sweetzyme enzyme and Mg2SO4. Lastly, as the energy balance tables have pointed out, the processes that the plant uses are not energy intensive, which means that only a small amount of steam needs to be bought. The processes of production are divided into 3 main steps. First are the physical processes which comprise the debarking, chopping, grinding and sieving. The next processes involve heat production, which include strong acid hydrolysis, neutralization, and vacuum evaporation. The next processes are the water dependent processes, which include filtration, ion exchange, and isomerization. The efficiency, however, must not be affected negatively by the layout of the plant. Lastly, the choices for equipment are crucial in the establishment of the plant since the cost estimation analysis will be largely dependent on the cost of total equipment purchased. For the cost analysis, the plant was found to be profitable for the entire test for profitability. The return of investment, net present worth, net return, payback period, IRR, cash flow and breakeven analysis show that the plant is profitable and will be earning after 1-2 years. The plant will be based on all the possible parameters and will be applicable to external changes if possible.
Submitted in partial fulfillment of the requirements in ChE 142 Chemical Engineering Plant Design.
Keywords: Fructose; Food processing plants -- Design and construction